CHALLENGES AND STRATEGIC APPROACHES IN DIGITAL VAT COLLECTION: EVIDENCE FROM INDONESIAN E-COMMERCE SECTOR - Sihaloho, Ulfah Oktarida (Universitas Muhammadiyah Makassar, 2025)
This research aims to analyze the implementation of digital VAT collection on e-commerce transactions in Indonesia, identify challenges, and propose strategies to address them. Focusing on PMK-60/PMK.03/2022, the study employs a descriptive qualitative approach, utilizing in-depth interviews with tax officials, e-commerce operators, and tax consultants, alongside documentation studies. Thematic analysis reveals key challenges, including regulatory inconsistencies, jurisdictional conflicts, inadequate technological infrastructure, system security vulnerabilities, and complexities in cross-border e-commerce compliance. Socio-economic disparities, such as the digital divide, further hinder inclusivity. The study emphasizes the need for comprehensive reforms, including regulatory strengthening, technological modernization, capacity building, and international collaboration. These findings offer actionable insights for policymakers to enhance digital VAT collection, promote equitable economic growth, and position Indonesia as a leader in digital tax policy innovation. The research contributes uniquely by integrating regulatory, technological, and socio-economic dimensions, addressing underexplored aspects of digital taxation in Indonesia.